(untitled) (Global Journal of Human-Social Science, 2014)
The impact of the staging environment on effectiveness of communication between the performer and the audience has remained contentious. The objective of this paper is to determine the effectiveness of plays about the Yorubas as presented elsewhere in the western world in projecting the Yoruba race. The paper is theoretically grounded on Richard Schechner’s Performance theories and used the documentary approach to sociology of drama to contentanalyze two selected performances in Europe and America. Findings showed that plays with Yoruba socio-cultural background face challenges when being staged in Western world because of its length, cast strength and staging condition which lower their aesthetic values and affect audience interpretation. The paper concluded that utilizing African theatre presentation style could be effective when performing in a foreign land. It therefore recommended its adoption and that cultural promoters should be conversant with the peculiarities of productions that projects Yoruba socio-cultural world-view.